1989
DOI: 10.1080/10408398909527507
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional improvement of cereals by fermentation

Abstract: Cereal grains form a major source of dietary nutrients for all people, particularly those in the developing countries. However, compared with animal foods, nutritional quality of cereal grains is inferior due to lower protein content, deficiency of certain essential amino acids, lower protein and starch availabilities, and the presence of some antinutritional factors. Fermentation of cereals for a limited period of time improves amino acid composition and vitamin content, increases protein and starch availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
2
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(157 citation statements)
references
References 99 publications
10
133
2
3
Order By: Relevance
“…These processes are known to activate phytases, which in turn hydrolyze phytate, rendering iron and zinc more available. During germination, endogenous phytase activity in cereals and legumes increases as a result of de novo synthesis and/or activation, resulting in reductions in inositol penta-and hexa-phosphates depending on the species and variety (Lorenz, 1980;Bartnick and Szafranska, 1987;Chavan and Kadam, 1989;Reddy et al, 1989). Reddy et al (1989) have reported reductions in phytate ranging from 36% for sprouted soya beans to 53% for germinated lentils.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are known to activate phytases, which in turn hydrolyze phytate, rendering iron and zinc more available. During germination, endogenous phytase activity in cereals and legumes increases as a result of de novo synthesis and/or activation, resulting in reductions in inositol penta-and hexa-phosphates depending on the species and variety (Lorenz, 1980;Bartnick and Szafranska, 1987;Chavan and Kadam, 1989;Reddy et al, 1989). Reddy et al (1989) have reported reductions in phytate ranging from 36% for sprouted soya beans to 53% for germinated lentils.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had reported increase (Chaven & Kadam, 1989; Doudu, Taylor, Belton, & Hamaker, 2003; El‐Hag et al., 2002; Pranoto, Anggrahini, & Efendi, 2013), while others observed decrease (Osman, 2011; Pranoto et al., 2013) in protein and/or some amino acids upon fermentation. It appears that most of these effects may not reflect actual changes but relative changes due to loss of dry matter as a result of microorganisms hydrolyzing and metabolizing carbohydrates and fats as source of energy.…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
“…Fermentation of pearl millet for 24 hr increased protein content due to loss of carbohydrates (Osman, 2011). Lysine, glycine, and arginine were reduced (Osman, 2011), while methionine was increased (Chaven & Kadam, 1989) after fermentation. While increase in protein may partly be attributed to loss of dry matter during fermentation, bacterial fermentation is known to increase lysine content in fermented grains (Hamad & Fields, 1979).…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
“…This reduction in phytate results in increase in amount of soluble iron, zinc and calcium (Blandino et al 2003). Apart from the extension of shelf life, fermentation also caused improvement in texture and flavour (Chavan and Kadam 1989). Martensson et al (2001) reported a non-dairy fermented product based on oat.…”
Section: Processing Of Oatsmentioning
confidence: 99%